(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
The COVID-19 epidemic has seriously harmed a number of sectors worldwide. A variety of raw materials, intermediate products, and finished goods availability and supply were given considerable consideration. Becoming irritated. The global supply chain (GSC), which over the years has shown itself to be very powerful and durable in the face of various shocks, is actually compromised. This paper uses critical reading, event causal analysis, and data to examine how COVID 19 has affected the effectiveness and responsiveness of CSS and makes a number of management recommendations to reduce risk and foster resilience across a range of industrial sectors. the branch. According to research, the COVID-19 pandemic has caused the majority of CSS, including the pharmaceutical, food, agricultural, electronics, and automotive industries, to operate with hitherto unheard-of disruption. Contrary to prior severe interruptions, COVID-19 has negatively impacted GSC’s operations at every level, causing considerable fluctuations in demand as well as significant volatility in the processes of manufacturing, processing, transportation, and logistics. According to the report, strengthening supply chain resilience is crucial for lowering vulnerability during disruptions. Additionally, the data demonstrates that the post-COVID-19 CSS will often be shorter as a result of enhanced tactics that place a greater emphasis on resettlement and back-shoring.